1989
DOI: 10.1159/000171878
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal Lavage in Gastric Carcinoma

Abstract: Peritoneal lavage was performed in 66 patients with gastric carcinoma to assess the amount of free tumor cells. 12/66 patients (18 %) proved to have free cancer cells. The intestinal type of carcinoma showed more frequently free tumor cells (8/12). There was no correlation between free cancer cells and the number of invaded lymph nodes. Patients with curative surgery but free cancer cells belong to the risk groups for early recurrences. Whether surgery on its own causes an increase in free tumor cells needs to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
16
0
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 5 publications
1
16
0
1
Order By: Relevance
“…In a subgroup of the Dutch Gastric Cancer Study (Bonenkamp et al, 1996), which is presently the single largest study of this topic in the Western world, among completely (R0-UICC) resected patients, there was detection rate of FPTC in 4% of patients, with an additional 1% diagnosed as suspicious for malignancy. In a smaller series, in tumours operated upon according to the guidelines of the GGCS (Roder et al, 1995), as was our study, Jaehne et al (1989) found a rate of 11% for FPTC. In the remaining studies of FPTC in gastric carcinoma, which are almost exclusively from Asia, rates of 14% (Koga et al, 1984) and 22% (Chen and Liu, 1994) are quoted for patients who have had a ÔcurativeÕ resection according to the guidelines of the JRSGC (Japanese Research Society for Gastric Cancer, 1981).…”
Section: Fptc: Frequency Conventional Cytologysupporting
confidence: 76%
See 2 more Smart Citations
“…In a subgroup of the Dutch Gastric Cancer Study (Bonenkamp et al, 1996), which is presently the single largest study of this topic in the Western world, among completely (R0-UICC) resected patients, there was detection rate of FPTC in 4% of patients, with an additional 1% diagnosed as suspicious for malignancy. In a smaller series, in tumours operated upon according to the guidelines of the GGCS (Roder et al, 1995), as was our study, Jaehne et al (1989) found a rate of 11% for FPTC. In the remaining studies of FPTC in gastric carcinoma, which are almost exclusively from Asia, rates of 14% (Koga et al, 1984) and 22% (Chen and Liu, 1994) are quoted for patients who have had a ÔcurativeÕ resection according to the guidelines of the JRSGC (Japanese Research Society for Gastric Cancer, 1981).…”
Section: Fptc: Frequency Conventional Cytologysupporting
confidence: 76%
“…However, it has been demonstrated in cases of definite tumour involvement of the gastric serosa without metastatic peritoneal implants, that only from 12% (Bonenkamp et al, 1996) to 22% (Chen and Liu, 1994) of cases have detectable free tumour cells. With an established peritoneal carcinosis, the rate of positive cytological diagnoses ranges from 50% (Jaehne et al, 1989) to 81% (Kaibara et al, 1987), with the provision that the rate of positive diagnosis is dependent on the extent of peritoneal carcinosis and, more importantly, on the presence of ascites.…”
Section: Fptc: Frequency Conventional Cytologymentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 Peritoneal dissemination is the most frequent pattern of recurrence in gastric cancer after potentially curative resection, and no efficient method of treatment is available. [5][6][7][8][9][10] Such recurrences may be attributable to possible intraperitoneal dissemination of malignant cells at the microscopic level, already present at the time of surgery, or due to surgical manipulations. [5][6][7]9,11 Peritoneal lavage as a diagnostic/staging method has not yet been definitely included in the management of gastrointestinal carcinomas, although pancreas, colon, and gastric cancers are quite often associated with ascites and/or intraperitoneal free tumor cells at the time of the initial diagnosis.…”
mentioning
confidence: 99%
“…After a median follow-up period of 12.5 months patients with disseminated tumor cells had a lower survival rate than patients without tumor cells. In der Vergangenheit wurde dem Tumorzellnachweis in der Peritoneallavage mit konventioneller zytologischer I Technik bei gastrointestinalen Tumoren Aufmerksamkeit iI geschenkt [12,16,26,28]. Mit der Etablierung und Ver-III IV besserung immunzytochemischer Techniken und der kommerziellen Herstellung zahlreicher Antik6rper ist es inzwischen jedoch m6glich, wesentlich empfindlicher Tumorzellen nachzuweisen [9,20,27].…”
unclassified